Advancing CAR-T therapy in prostate cancer: overcoming the tumor microenvironment and enhancing efficacy - Zhou, Zhongze; Lao, Yongfeng; Zhao, Kun; Cheng, Long; Xiao, Xi; Li, Wenxuan; Liu, Shuai; Kong, Xiangbin; Dong, Zhilong (Frontiers in Oncology, 2026)
BackgroundProstate cancer (PCa) is one of the most common malignancies in men, and metastatic castration-resistant PCa (mCRPC) has limited treatment options. While chimeric antigen receptor T (CAR-T) therapy has revolutionized treatment of hematologic cancers, its efficacy in PCa is constrained by factors such as scarce tumor-specific antigens, an immunosuppressive tumor microenvironment (TME), antigen heterogeneity, and safety issues (e.g., cytokine release syndrome).MethodsWe performed a comprehensive literature review of CAR-T therapy in PCa. We summarized known PCa-specific CAR targets, identified major TME-related and technical barriers, and highlighted recent advances in CAR engineering (including armored CAR-T cells, gene editing, and metabolic reprogramming) as well as combination approaches with other therapies.ResultsEmerging strategies show promise for overcoming these obstacles. Next-generation CAR designs, such as cytokine-armed CAR-T cells, may enhance T cell infiltration and persistence despite the suppressive TME. Modulating tumor metabolism and immune checkpoints can reverse T cell exhaustion. Multi-antigen CARs and targeted gene edits (for example, PD-1 disruption) may limit antigen escape. Early clinical trials in PCa have demonstrated CAR-T cells specifically recognizing prostate-associated antigens and eliciting antitumor immune responses, although durable remissions remain rare.ConclusionCAR-T therapy for prostate cancer is a rapidly advancing field. This review provides an updated perspective on CAR-T targets, engineering strategies, and combination approaches in PCa. Ongoing innovations in CAR design and therapeutic combinations offer the potential to develop more effective and durable CAR-T treatments for advanced prostate cancer.